Penyelesaian Kredit Bermasalah dengan Metode Restrukturisasi Pada Koperasi Simpan Pinjam Merta Sari di Denpasar Utara - I Ketut Gede Suardana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2022)
The existence of cooperative organizations is very beneficial for the economic interests of community members. The purpose of this study was to analyze the causes of non-performing loans in Merta Sari Savings and Loans cooperatives in North Denpasar and to discuss problem solving through restructuring methods at Merta Sari Savings and Loans cooperatives in North Denpasar. The type of research used is empirical law. This study uses a conceptual and sociological case approach. Sources of data are both primary data which is field data (field research), as well as secondary data from the library (library research). The data collection technique used interview techniques at the research location, namely the Merta Sari Savings and Loans Cooperative in North Denpasar. The results of the study explained that the factors that caused the occurrence of non-performing loans in the Merta Sari Savings and Loans Cooperative were several things that became a problem in completing the loan, there were several debtors who experienced a disaster which hit the debtor's business so that the debtor suffered losses and lacked good faith from the debtor so that it was not direct impact on the smooth running of ongoing credit payments and the lack of a management in financial management. In handling non-performing loans, the Merta Sari Savings and Loans Cooperative takes steps to resolve non-performing loans using the credit restructuring method to reduce the level of non-performing loans that occur in the Merta Sari Savings and Loans Cooperative. Credit restructuring is an improvement effort made to meet its obligations